1994
DOI: 10.1063/1.356063
|View full text |Cite
|
Sign up to set email alerts
|

Site selectivity in Fe doped β phase NiAl

Abstract: Articles you may be interested inSite-selective investigation of site symmetry and site occupation of iron in Fe-doped lithium niobate crystals

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
9
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 7 publications
3
9
0
Order By: Relevance
“…For completeness, these results, from Refs. [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42], are provided in Table 3, although some of the experimental studies cited correspond only to equiatomic alloys. The last two columns show the results of BANN and MCAS simulations after annealing at room temperature.…”
Section: Resultsmentioning
confidence: 98%
“…For completeness, these results, from Refs. [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42], are provided in Table 3, although some of the experimental studies cited correspond only to equiatomic alloys. The last two columns show the results of BANN and MCAS simulations after annealing at room temperature.…”
Section: Resultsmentioning
confidence: 98%
“…The gain in ductilization or softening of the alloy disappeared beyond 0.5 at.% in single crystal Ni 50 Al 50 alloy [9]. The view of Ikeda [8] who assumed that Fe and Ni compete randomly for "Al-type" sites, leading to the suggestion that for Fe 1 Ni 50 Al 49 one would expect to find 50 times more Ni than Fe atoms forced into the Al sublattice, was contradicted by Chartier et al [10] who claimed that Fe occupied exclusively Al-sublattice. These seemed to be supported by earlier studies which pointed to the fact that the site occupation tendency determined trends in the development of hyperfine interactions in nickel and Fe alumnides and could be used to make distinctions in doped NiAl system [11,12].…”
mentioning
confidence: 92%
“…With the Al-rich side (>50 at.% Al), vacancies instead of Al anti-sites are formed on the Ni sublattice leading to higher hardening than the Ni anti-site defects at the Al sublattice [6,7]. Further, substituting atoms site occupancy tendencies in stoichiometric and off stoichiometric alloys with microalloying or doping using especially transition metals have been studied with the observation that limited ductilization was recorded in β phase Ni 50 Fe x Al 50-x for dope atoms concentrations up to a few tenths of 1 at.% [8][9][10][11]. The gain in ductilization or softening of the alloy disappeared beyond 0.5 at.% in single crystal Ni 50 Al 50 alloy [9].…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…It has been observed that ductilization from doping is higher in the transition metal (TM)-rich NiAl than in the Al-rich alloys. For instance, when Fe atoms are used to dope Ni-rich alloys designated as Fe x Ni 50 Al 50ÿx [2], they occupy exclusively the Al sublattice. This means that Fe substitutes into sites with eight TM near neighbors.…”
Section: Introductionmentioning
confidence: 99%